Vaccine exposure during pregnancy among privately and publicly insured women in the United States, 2016–2018. Issue 41 (1st October 2021) - Moll, Keran; Wong, Hui-Lee; Fingar, Kathryn; Zhou, Cindy Ke; Lu, Michael; Hu, Mao; Hobbi, Shayan; Burrell, Timothy; Baer, Bethany; Simard, Julia; Obidi, Joyce; Chillarige, Yoganand; et al.
Highlights: Half or more of pregnancies did not receive the recommended flu or Tdap vaccine. Exposure to MMR (contraindicated) and HPV (not recommended) vaccines was rare. Most maternal Tdap vaccinations occurred during the recommended gestational window. Abstract: Background: Vaccine use during pregnancy affects maternal and infant health. Many women do not receive vaccines recommended during pregnancy; conversely, inadvertent exposure to vaccines contraindicated or not recommended during pregnancy may occur. We assessed exposure to two recommended vaccines and two vaccines not recommended during pregnancy among privately and Medicaid-insured women in the United States. Methods: This study includes a retrospective cohort of pregnancies in women aged 12–55 years resulting in live birth, spontaneous abortion, or stillbirth identified in the IBM® MarketScan® Commercial, Blue Health Intelligence® (BHI®) Commercial, and IBM MarketScan Multi-State Medicaid Databases from August 1, 2016, to December 31, 2018. Gestational age at vaccination was determined using a validated algorithm. We examined vaccines (1) recommended by the Centers for Disease Control and Prevention Advisory Committee on Immunization Practices (ACIP) (tetanus, diphtheria, and acellular pertussis [Tdap]; inactivated influenza) and (2) not recommended (human papillomavirus [HPV]) or contraindicated (measles, mumps, and rubella [MMR]). Results: We identified 496, 771 (MarketScan Commercial), 858, 961 (BHI), and 289, 573 (MarketScan Medicaid) pregnancies (approximately 75% aged 20–34 years). Across these three databases, 52.1%, 50.3%, and 31.3% of pregnancies, respectively, received Tdap, most often at a gestational age of 28 weeks, and influenza vaccination occurred in 32.1%, 30.8%, and 18.0% of pregnancies, respectively. HPV vaccination occurred in < 0.2% of pregnancies, mostly in the first trimester among women aged 12–19 years, and MMR was administered in < 0.1% of pregnancies. Use of other contraindicated vaccines per ACIP (e.g., varicella, live attenuated influenza) was rare. Conclusion: Maternal vaccination with ACIP-recommended vaccines was suboptimal among privately and Medicaid-insured patients, with lower vaccination coverage among Medicaid-insured pregnancies than their privately insured counterparts. Inadvertent exposure to contraindicated vaccines during pregnancy was rare. This study evaluated only vaccinations reimbursed among insured populations and may have limited generalizability to uninsured populations.